Prevalence, and Pattern of Hypoxic Ischemic Encephalopathy on Magnetic Resonance Imaging among Pediatric patients - Marya Hameed, Hayat Bozdar,Sadia Khurshid, Humera Sohail, Fatima Siddiqui, Noor Fatima, Ameet Kumar Jesrani (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypoxic Ischemic Encephalopathy is a frequently encountered occurrence in a pediatric setting and more prevalent in the low middle income countries. Magnetic resonance imaging (MRI) is considered a reliable source of investigation. Our study determined the imaging findings and cause of Hypoxic ischemic encephalopathy in children referred for MR Imaging to our radiology department. Study design: A prospective cross-sectional study. Place and duration of study: Our prospective cross-sectional study was conducted at a pediatric tertiarycare hospital, of Karachi Pakistan from 1st November 2021 to 30th October 2022. Methods: Our study included children from newborns to 16 years of age who either had a history of fits, abnormal APGAR score, delayed cry or delayed milestones. The brain MRI was performed on 1.5 tesla scanner with a standard protocol and interpreted by Experienced Radiologists Findings were recorded on anExcel Sheet and data was analyzed on SPSS version 26. Our study included children from newborns to 16 years of age who were at risk of hypoxic insult and were born to mothers who had hypertension, diabetes milletus, history of maternal substance abuse and maternal history of fits history of fits and children who had a history of fits, abnormal APGAR score, delayed cry and/or delayed milestones. Children who were born via instrumental delivery were excluded from our study. Result: A total number of 187 patients were included in our study with 98 males and 89 females. The most common age group involved was from age >1 year to 5 years (50.3%). The most common presenting complaints included delayed milestones (63.6%) and fits (59.9%), delayed cry (52.4). On examination 42.2% had microcephaly. One-third of the patients had a positive maternal history for diabetes mellitus, hypertension and anemia. APGAR score was checked at 1 minute and 5 minute which showed the most common APGAR score of 3-6 which was seen in 81.8% of the patients. On MR Imaging 54.5% had periventricular leukomalacia, 35.3% had deep gray matter involvement, 3.7% had germinal matrix hemorrhage, and only 1.6% had watershed infarcts. A statically significant association was seen between gestation at birth and periventricular leukomalacia (P=<0.5). Conclusion: Hypoxic Ischemic Encephalopathy is a common occurrence in our society and MRI is the recommended modality due to its sensitivity and superior soft-tissue resolution. In developing countries due to a lack of proper facilities and awareness, there is an increased incidence of HIE which leads to increased morbidity therefore increasing awareness and early diagnosis is of utmost importance. Keywords: Hypoxic ischemic encephalopathy, Magnetic Resonance Imaging, Pediatric population